Effect of Magnetic Field and Hybrid Nanofluid on Heat Transfer Through a Microchannel - Ali Salehin; Arash Mirabdolah Lavasani; Mohammad Nimafar; Gholamreza Salehi; Mohammad Vahabi (مجله مدل سازی در مهندسی)
This numerical study examines the influence of a magnetic field and hybrid nanofluid on heat transfer in a microchannel. The microchannel with a square cross-section and dimensions of 0.5 × 0.5 mm, is situated within a cube-shaped piece. A heat flux of 3750 W/m2 and a constant magnetic field of 1 tesla, perpendicular to the flow, are applied. The research employs a hybrid nanofluid, with soybean oil as the base fluid and hybrid nanoparticles comprising 75% magnesium oxide and 25% aluminum dioxide, at a volume fraction of 1 to 4%. The laminar fluid flow is used, and the volume flow inside the microchannel is 0.01, 0.025, 0.05, 0.075, and 0.1 ml/s, respectively. The numerical analysis utilizes a single-phase model, and the finite volume method is employed to solve the equations. The results indicate that applying boundary conditions of forced convection with ambient air on the five sides of the cube-shaped piece can enhance the convective heat transfer coefficient by 8.3% to 50%, compared to the absence of force convection in the faces under certain conditions.